Pengaruh Penggunaan Aplikasi Pembelajaran Bahasa terhadap Motivasi Belajar Bahasa Asing Siswa SMA Negeri 1 Mataram - Anjas Pratama; Nur Awfiah Nadhila (Journal of Language Studies, 2026)
The rapid development of digital technology has transformed foreign language learning in secondary education. Language learning applications are increasingly used to enhance student engagement and learning motivation. This study aims to examine the effect of language learning applications on foreign language learning motivation among students of SMA Negeri 1 Mataram. The research employed a quantitative approach using an explanatory survey design. The sample consisted of 120 eleventh-grade students selected through stratified random sampling. Data were collected using a validated and reliable Likert-scale questionnaire measuring learning motivation. Data analysis was conducted using simple linear regression. The results indicate that the use of language learning applications has a positive and significant effect on students’ foreign language learning motivation. Applications featuring gamification, immediate feedback, and autonomous learning significantly enhance both intrinsic and extrinsic motivation. These findings support established theories of language learning motivation and are consistent with previous studies on technology-enhanced language learning. The study recommends the systematic integration of language learning applications into foreign language instruction at the senior high school level.